Concentração de renda e política tributária: análise a partir dos grandes números da Receita Federal (2007-2017) - Santos, Rodrigo Cesar Simão Alves dos (2021)
The objective of this paper is to analyze how income concentration is related to tax policy in Brazil, where it seeks to assess the distributive impacts of an increase in the progressivity of taxes. Through the bibliographic review of the debate on income distribution in Brazil, it is observed that the interpretations about this characteristic of the Brazilian economy oscillated between the impact of salary policies and the educational aspects of the population within the theory of human capital. Recent research shows that the focus of the discussion on income distribution should be turned to the richest groups in society. To measure the gains in distributive terms of an increase in progressive taxation, based on the discussion of profits and dividends, the data provided by the “Receita Federal” were used because they can be used within the concept of tax income. The construction of the Gini coefficients is as follows: first, there is a large concentration of income within the data provided by the “Receita Federal”, indicating similarity with recent research on the top of the distribution. This allows the use of data as a proxy to measure distributive gains with changes in the taxation of the wealthiest groups and to envision the problem of “pejotização” in Brazilian society. Secondly, there are the distributive gains from the introduction of a progressive rate on the exempt income category: reduction of the Gini coefficient by 3.09% for all taxpayers and 1.97 % for recipients of profits and dividends together with the maintence of the downward trend of the indicator. Thus, it seeks to contribute so that the tax reform proposals also consider equity aspects on the form of collection. Keywords: